Concordance of angiographic and electrocardiographic indexes of microvascular obstruction: myocardial haemorrhage role. Issue 5 (May 2016) - Niccoli, Giampaolo; Cosentino, Nicola; Spaziani, Cristina; Loria, Valentina; Fracassi, Francesco; Roberto, Marco; Calvieri, Camilla; Lombardo, Antonella; Natale, Luigi; Napolitano, Carmela; Mandurinoa, Alessandro; Burzotta, Francesco; et al.
Abstract : Background: Angiographic and electrocardiographic (ECG) indexes of microvascular obstruction (MVO) have been described. We aimed at assessing by cardiac magnetic resonance (CMR) anatomical features underlying concordance between them. Methods: Forty-one patients were enrolled. Patients presented with neither angiographic nor ECG indexes of MVO (without MVO) (44%), with either angiographic or ECG indexes of MVO (discordant with MVO) (22%) or with both angiographic and ECG indexes of MVO (concordant with MVO) (34%). All patients underwent in-hospital CMR. Echocardiographic data obtained after 6 months were compared with those obtained in hospital. Results: Concordant patients with MVO had larger infarct size, lower myocardial salvage index and higher rate of myocardial haemorrhage (all assessed by CMR) [33% (25–41%), 15% (10–29%) and 88%, respectively] as compared with patients without MVO [12% (9–16%), 66% (52–79%) and 0%; Bonferroni-adjusted P < 0.001, Bonferroni-adjusted P < 0.001 and P < 0.001, respectively], or with discordant ones [25% (21–39%), 35% (20–48%) and 7%; Bonferroni-adjusted P = 0.03, Bonferroni-adjusted P = 0.002 and P = 0.04, respectively]. After 6 months, ejection fraction significantly decreased in concordant patients with MVO ( P < 0.001) without significant changes in the other groups. Conclusions: Concordance of angiographic and ECG indexes of MVO reflects more severe myocardial damage translating into unfavourable left ventricular remodelling. Abstract : Supplemental Digital Content is available in the text